Power Point-based Android English Learning Multimedia in Teaching Descriptive Text; Developing and Feasibility Study - Pratama, Raka Widi; Junaedi, Ahmad; Danial, Muhammad Danial (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research aims to develop and produce interactive learning media based on android applications in English subjects. This type of research is research and development that refers to the 4D development model modified into 3D. The subjects of this research were first grade students of SMPN 3 Majene. The instruments used in this study were (1) media expert validation sheet to measure media feasibility, (2) product expert validation sheet to measure media feasibility, and (3) student response questionnaire to find out students' opinions on the attractiveness of the developed media. The results of the research are: (1) Development of interactive learning media based on android. (2) Learning media is declared feasible by media expert validators with a percentage of 92% in the very feasible category and experts with a percentage of 94% including the very feasible category. (3) The learning media is declared interesting based on the results of the analysis of student response questionnaires, which is 80%. At the end of this study, it can be inferred that Power Point-based Android English Learning Multimedia is feasible and ready to assist English teachers and students to gain better English learning.